2022
DOI: 10.1021/acscatal.2c03861
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Protoboration of 1,3-Diynes as a Platform for Iterative Functionalization

Abstract: This paper presents the protoboration of 1,3-diynes as a platform for the iterative functionalization of various groups on enynes and dienes. Synthetic approaches to targets with high complexity are directed toward using small, modular building blocks similar to a “Lego” construction using iterative chemistry and automated synthesis. Organoboron compounds are currently in the spotlight for achieving these goals. Here, we report an operationally simple, regioselective protoboration of 1,3-diynes using a mixed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…In this regard, integrating boron moiety into organic π-conjugated 1,3-enyne frameworks will further increase their structural diversity and synthetic application potential . Recently, transition-metal-catalyzed two-component reactions or transition-metal-free stereoselective hydroboration of 1,3-diynes have been developed, which provide an elegant strategy for the synthesis of trisubstituted boronated organic π-conjugated 1,3-enyne frameworks . However, to the best of our knowledge, the synthesis of tetrasubstituted boronated organic π-conjugated 1,3-enyne frameworks by three-component borylation reactions has not been well developed.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, integrating boron moiety into organic π-conjugated 1,3-enyne frameworks will further increase their structural diversity and synthetic application potential . Recently, transition-metal-catalyzed two-component reactions or transition-metal-free stereoselective hydroboration of 1,3-diynes have been developed, which provide an elegant strategy for the synthesis of trisubstituted boronated organic π-conjugated 1,3-enyne frameworks . However, to the best of our knowledge, the synthesis of tetrasubstituted boronated organic π-conjugated 1,3-enyne frameworks by three-component borylation reactions has not been well developed.…”
Section: Introductionmentioning
confidence: 99%
“…12 Boron-enyne is an important scaffold for the generation of enediyne systems. There are several reports in the literature on the synthesis of boryl-functionalized enynes catalyzed with metals such as Cu, Ni, Co and Pt [13][14][15][16][17][18][19][20] or with phosphine. 21 However, these reactions are neither regioselective nor stereoselective.…”
Section: Introductionmentioning
confidence: 99%
“…18 A similar approach was applied by Ganesh, who used a mixed diboron reagent. 19 Recently, Santos et al reported the selective synthesis of ( Z )-1,3-enynes via the hydrolysis of borylenyne intermediates. 20 All the described protocols utilized multicomponent catalytic systems that were generated in situ or strictly maintained reaction conditions.…”
mentioning
confidence: 99%
“…The synthesis of a regioisomer with the boryl group at the external C sp 2 carbon is more challenging and is limited only to three examples. 18,19,21…”
mentioning
confidence: 99%
See 1 more Smart Citation